Statistical learning of a tonal language: the influence of bilingualism and previous linguistic experience - Wang, Tianlin; Saffran, Jenny R. (Frontiers in Psychology, 2014)
While research shows that adults attend to both segmental and suprasegmental regularities in speech, including syllabic transitional probabilities as well as stress and intonational patterns, little is known about how statistical learning operates given input from tonal languages. In the current study, we designed an artificial tone language to address several questions: Can adults track regularities in a tonal language? Is learning enhanced by previous exposure to tone-marking languages? Does bilingualism affect learning in this task? To address these questions, we contrasted the performance of English monolingual adults (Exp. 1), Mandarin monolingual and Mandarin-English bilingual adults (Exp. 2), and non-tonal bilingual adults (Exp.3) in a statistical learning task using an artificial tone language. The pattern of results suggests that while prior exposure to tonal languages did not lead to significant improvements in performance, bilingual experience did enhance learning outcomes. This study represents the first demonstration of statistical learning of an artificial tone language and suggests a complex interplay between prior language experience and subsequent language learning.